Actin cytoskeletal defects in immunodeficiency. Issue 1 (10th October 2013) - Moulding, Dale A.; Record, Julien; Malinova, Dessislava; Thrasher, Adrian J.
Summary: The importance of the cytoskeleton in mounting a successful immune response is evident from the wide range of defects that occur in actin‐related primary immunodeficiencies (PIDs). Studies of these PIDs have revealed a pivotal role for the actin cytoskeleton in almost all stages of immune system function, from hematopoiesis and immune cell development, through to recruitment, migration, intercellular and intracellular signaling, and activation of both innate and adaptive immune responses. The major focus of this review is the immune defects that result from mutations in the Wiskott‐Aldrich syndrome gene ( WAS ), which have a broad impact on many different processes and give rise to clinically heterogeneous immunodeficiencies. We also discuss other related genetic defects and the possibility of identifying new genetic causes of cytoskeletal immunodeficiency.